2005
DOI: 10.1007/978-3-540-30576-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Constructible Huge Graphs That Preserve First Order Properties of Random Graphs

Abstract: Abstract. We construct efficiently computable sequences of randomlooking graphs that preserve properties of the canonical random graphs G(2 n , p(n)). We focus on first-order graph properties, namely properties that can be expressed by a formula φ in the language where variables stand for vertices and the only relations are equality and adjacency (e.g. having an isolated vertex is a first-order property ∃x∀y(¬edge(x, y))). Random graphs are known to have remarkable structure w.r.t. first order properties, as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Multiplicative characters of finite fields display highly pseudorandom properties, and yet are tractable for analysis (through tools like the Weil-bound for character sums). These pseudorandom properties of characters have been used in the construction of some remarkable pseudorandom graphs (the Paley graphs, see [8,15]), as well as other combinatorial objects likebiased sets [1,2]. It is therefore natural to ask whether pseudorandom constructions based on multiplicative characters can be executed in AC 0 (⊕).…”
Section: Residuositymentioning
confidence: 99%
“…Multiplicative characters of finite fields display highly pseudorandom properties, and yet are tractable for analysis (through tools like the Weil-bound for character sums). These pseudorandom properties of characters have been used in the construction of some remarkable pseudorandom graphs (the Paley graphs, see [8,15]), as well as other combinatorial objects likebiased sets [1,2]. It is therefore natural to ask whether pseudorandom constructions based on multiplicative characters can be executed in AC 0 (⊕).…”
Section: Residuositymentioning
confidence: 99%
“…Therefore, the standard version of the 0-1 law implies that R(k, n) → 0 as n → ∞ for any fixed k. Naor, Nussboim, and Tromer [58] showed that R(log n−2 log log n, n) → 0. Another result in [58] states that one can choose p(n) = 1/2 + o(1) and k(n) = (2+o (1)) log n such that the probability that G n,p has a k(n)-clique is bounded away from 0 and 1. Thus for this probability p(n) the 0-1 law does not hold with respect to formulas of depth k(n).…”
Section: Bounds For Treesmentioning
confidence: 99%
“…We now prove Part 1. Like the proof in [58] we use the extension property, but we argue in a slightly different way. Proof of Part 1.…”
Section: Bounds For Treesmentioning
confidence: 99%
“…Another approach was taken by Naor et al in [36] where they let the quantifier depth to go to infinity with n and considered the maximal quantifier depth for which the Zero-One law for G(n, p) with constant p still holds. This gives rise to a few more questions.…”
Section: Concluding Remarks and Open Questionsmentioning
confidence: 99%